Chinese Stroke Association guidelines for clinical management of cerebrovascular disorders: executive summary and 2019 update of the management of high-risk population. Issue 3 (13th August 2020) - Wang, Yilong; Han, Shangrong; Qin, Haiqiang; Zheng, Huaguang; Jiang, Bin; Cao, Yong; Gao, Yuan; Guan, Ling; Jia, Qian; Jiang, Yong; Jiao, Yuming; Li, Shuya; et al.
Abstract : Aim: Cerebrovascular disease is the leading cause of death and disability in China, causing a huge burden among patients and their families. Hence, stroke prevention is critical, especially in the high-risk population. Here, we present the evidence-based guideline suitable for the Chinese population. Methods: Literature search of PubMed and Cochrane library (from January 1964 to June 2019) was done. After thorough discussion among the writing group members, recommendations were listed and summarised. This guideline was reviewed and discussed by the fellow writing committees of the Chinese Stroke Association's Stroke. Results: This evidence-based guideline was written in three parts: controlling the risk factors of stroke, utilisation of antiplatelet agents and assessing the risks of first-ever stroke. All recommendations were listed along with the recommending classes and levels of evidence. Conclusions: This guideline provides recommendations for primary prevention of cerebrovascular disease among high-risk population in China. Controlling related risk factors, appropriately using antiplatelet agents, assessing the risk of developing first-ever stroke should help reduce the rate of cerebrovascular disease in China.